Spatially explicit forecasting of frost damage in German apple cultivation under changing climatic conditions - Christine Schmitz; Lars Caspersen; Johannes Kopton; Katja Schiffers; Eike Luedeling (European Journal of Agronomy, 2026)

Climate change shifts almond bloom dates in Afghanistan - Atifullah Shinwari; Lars Caspersen; Katja Schiffers; Eike Luedeling (International Journal of Biometeorology, 2026)
Climate change is reshaping the spring phenology of temperate fruit and nut trees worldwide, causing uneven bud break and yield losses across major production regions. Almond trees, including those cultivated in Afghanistan, are susceptible to these shifts. Afghanistan produces over 50 almond varieties, with official exports worth around USD 40 million in 2024. Yet, this value remains below potential due to multiple challenges along the value chain, one of which is the ongoing temperature increase affecting phenology and yields. We projected the flowering dynamics of 51 Afghan almond cultivars using long-term temperature data (1980–2023) and phenological observations (2011–2023). Two historical reference periods (1980 and 2020) and future projections for 2050 and 2085 were simulated under three Shared Socioeconomic Pathway (SSP) scenarios (SSP1-2.6, SSP2-4.5, SSP5-8.5) based on 15 General Circulation Models. Bloom predictions were obtained using the PhenoFlex modeling framework with a recently developed combined-fitting approach. The model accurately reproduced observed bloom patterns, achieving a Root Mean Square Error of Prediction below four days for all cultivars. Compared to 1980, bloom dates advanced by roughly two weeks by 2020. Future projections suggest additional advances of up to 16 days for most cultivars, whereas a few exhibited delays of up to 12 days. Pronounced shifts exceeding seven days were found in about 25% of all predictions driven by specific cultivars, especially by 2085 under intermediate and high-emission scenarios. These results emphasize the significant and ongoing changes in almond phenology, highlighting the importance of adaptive management to sustain production and export potential under future climates.

Rethinking Model Transferability: Validity Domains as a New Approach to Delineate the Limits of Bloom Date Projections - Julian N. Bauer; Katja Schiffers; Lars Caspersen; Hisayo Yamane; Eike Luedeling (Global Change Biology, 2026)
Accurately predicting future events under novel environmental conditions is a central challenge in modeling, especially when no validation data are available. While model transferability is often discussed through the concept of a “forecast horizon,” we expand this framework by introducing the concept of “validity domains.” These consider not only the extrapolation distance from the calibration data but also the absolute position of calibration and application conditions along an environmental gradient. Using phenological observations from Japanese Yoshino cherry ( Prunus × yedoensis ) across a climate gradient in Japan, we calibrated process‐based and machine learning models for each of 48 locations and validated them with data from all other locations. Interpolating model performance metrics yielded a continuous synthetic surface of predictive accuracy across the full observed temperature range, from which we delineated model‐specific validity domains and assessed how transferability depends on both model type and calibration environment. Our findings show that process‐based models retain broader validity when calibrated in colder environments but degrade in warmer settings. In contrast, machine learning models exhibit narrower but more consistent validity across the gradient. These systematic differences reveal that the location of calibration and the structure of the model fundamentally shape its reliability under new conditions. By identifying where prediction errors remain below a context‐specific validity threshold, our approach provides a robust framework for assessing model applicability under shifting climate conditions. Mapping validity domains offers practical guidance for model selection and allows quantifying how far models can be pushed before their predictions become unreliable.

Combining temperate fruit tree cultivars to fit spring phenology models - Lars Caspersen; Katja Schiffers; Katherine Jarvis-Shean; Eike Luedeling (International Journal of Biometeorology, 2026)
Phenological datasets for temperate fruit trees are often short, fragmented and geographically restricted, which hampers the development of cultivar-specific spring phenology models. To address this, we propose a novel calibration approach (“combined-fitting”), which pools observations from several cultivars of the same species, distinguishing between shared and cultivar-specific parameters. This method requires fewer observations per cultivar and allows jointly analyzing cultivars of the same species. We evaluate combined-fitting using the PhenoFlex framework, comparing it to a baseline model and to models that are fitted only with data for single cultivars (“cultivar-fit”). Our analysis is based on flowering data from nine almond, six apricot and six sweet cherry cultivars across Mediterranean (Spain, Morocco, Tunisia) and German climates. The combined-fit model failed to achieve higher prediction accuracy compared to the cultivar-fit and the baseline approach, as evidenced by similar root mean square errors across the data splits and calibration dataset sizes. When comparing the estimated parameters of the chill and heat accumulation submodels, we observed a large variation among cultivars of the same species in the cultivar-fit models. In contrast and by design, the combined-fit yielded only one parameter set for cultivars of the same species. Our findings demonstrate that integrating data from multiple cultivars can yield spring phenology models with high accuracy. Even though the combined-fit approach did not outperform the cultivar-fit approach, combined-fitting offers a practical solution for spring phenology modeling with limited datasets and facilitates comparison across cultivars of the same species.

Cultivar plasticity in temperate fruit trees across the Mediterranean region: Different combinations of chill and heat lead to dormancy release - Alvaro Delgado; David Ruiz; Javier Rodrigo; Eike Luedeling; Eduardo Fernandez; Hajar Mojahid; Brenda I. Guerrero; M. Engracia Guerra; Nestor Santolaria; Patricia Irisarri; Jose A. Egea; Lars Caspersen; et al. (European Journal of Agronomy, 2026)

Contrasting responses to climate change – predicting bloom of major temperate fruit tree species in the Mediterranean region and Central Europe - Lars Caspersen; Katja Schiffers; Antonio Picornell; Jose A. Egea; Alvaro Delgado; Adnane El Yaacoubi; Haïfa Benmoussa; Javier Rodrigo; Erica Fadón; Mehdi Ben Mimoun; Mohamed Ghrab; Ossama Kodad; et al. (Agricultural and Forest Meteorology, 2025)

Spring phenology projections for apples in southwestern Germany indicate persistent frost risk levels - Lars Caspersen; Katja Schiffers; Anton Milyaev; Daniel Neuwald; Eike Luedeling (Agricultural and Forest Meteorology, 2025)

Cross-regional validation of the PhenoFlex framework for flowering date prediction in apple: A study across Germany and Spain - Hajar Mojahid; Lars Caspersen; Alvaro Delgado; Enrique Dapena; Eike Luedeling; Katja Schiffers; Eduardo Fernandez (Agricultural and Forest Meteorology, 2025)

Historical and future winter chill for temperate fruit and nut trees in Afghanistan - Atifullah Shinwari; Lars Caspersen; Katja Schiffers; Eike Luedeling (Climatic Change, 2025)
Temperate fruit trees require exposure to chill and heat conditions to overcome the dormant period in winter and resume growth in spring. Rising temperatures due to climate change have already impacted winter chill accumulation in horticulturally vital growing regions worldwide. Afghanistan’s intra-regional differences make the country favorable for producing a wide range of fruits and nuts, which constitute approximately 30% of the country’s total export earnings. However, expected future temperature increases may be detrimental to the trees’ ability to fulfill their chilling requirements. To quantify this risk, we computed and mapped historical and future chill accumulation in Afghanistan. For this purpose, we used long-term daily temperature data from 1980 to 2020 for 51 hydrometeorological stations across the country. Based on the temperature data, we produced four future Shared Socioeconomic Pathway (SSP) scenarios (SSP126, SSP245, SSP370, and SSP585) for five General Circulation Models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6). We used the RMAWGEN weather generator to produce 100 synthetic realizations of weather records for historical (1980, 1990, 2000, 2010, and 2020) and future conditions (2035–2065 and 2070–2100). We quantified winter chill using the Dynamic Model. Additionally, we computed Safe Winter Chill (SWC), which is defined as the level of chill that is expected to be exceeded in 90% of years. We find that SWC has decreased in historical scenarios in the low-lying regions mainly in the eastern, southern, and parts of the northern regions, and is projected to further decrease in the future. This reveals a possible future chill risk for high chill-requiring cultivars of different fruit and nut species, including apricot, peach, plum, pistachio and almond, in these regions. In contrast, we record an increase in SWC in the northern and central regions, suggesting these regions as potentially favorable for high-chill species in the future. Our findings support fruit and nut growers in Afghanistan in adapting their orchards to match chill requirements of species and cultivars to the expected future winter chill.

Participatory modelling of scenarios to restore nitrogen cycles in a nutrient-saturated area - Bernou Zoë van der Wiel; Lars Caspersen; Cory Whitney; Corina van Middelaar; Jan Weijma; Florian Wichern (Science of The Total Environment, 2024)

Warm winters challenge the cultivation of temperate species in South America—a spatial analysis of chill accumulation - Eduardo Fernandez; Lars Caspersen; Ilja Illert; Eike Luedeling (Climatic Change, 2021)
Winter chill accumulation plays a crucial role in determining the moment of bud burst in temperate fruit and nut trees, and insufficient chill can greatly limit yield potentials. To assess future cultivation options for such species in South America, we estimated winter chill through a spatial analysis. We used historical data (1980–2017) from 158 weather stations to calibrate a weather generator and produce temperature data for 10 historical and 60 future scenarios. We computed Safe Winter Chill (SWC, corresponding to the 10th quantile of a chill distribution) for the period 1980–2017 and for all historical and future weather scenarios and developed a framework to interpolate SWC for the continent using the Kriging method. To improve the interpolation, we applied a 3D correction model based on two co-variables (means of daily temperature extremes in July). Our results suggest important chill declines in southern Brazil and central Chile. By 2050 under the global warming scenario RCP4.5 (Representative Concentration Pathway), absolute SWC in these regions may reach a median of 18.7 and 39.6 Chill Portions (CP), respectively. Projections are most alarming for a strong global warming scenario (RCP8.5). In southern South America, adequate SWC levels of about 60 CP may be expected even under the RCP8.5 scenario. Our results highlight the need for climate change adaptation measures to secure temperate fruit production in important growing regions of South America. The procedure we developed may help farmers and practitioners across South America estimate future SWC to adapt their orchards to future challenges.